Characteristics and Beauty of Modern Poetry by Ibn Zaidun - Nuruddin, Ahmad; Syaifuddin, A. (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2023)
This study aims to analyze the characteristics and beauty of modern poetry by Ibn Zaidun, who was one of the leading poets in modern times in Andalusia during the reign of the Umayyads. This research is a library research with a qualitative descriptive research method. The data and data sources are words or sentences that are included in the poetry section of Ibn Zaidun's work. In this study, we will discuss in detail the characteristics and beauty of Ibn Zaidun's poetry. The results of this study indicate that Ibn Zaidun is a poet who writes a lot about love poetry (al-Ghazal), even though this poem still contains sub-themes such as praise (al-Madh). Of the several themes of this poem, Walladah is the one who inspired the writing of Ibn Zaidun's poems. The form of the beauty of poetry that will be studied is in terms of theme, emotion ('athifah), imagination (khayāl), style of language and poetry of poetry which includes the science of balaghah, 'arudl, and qawafi. It is from these studies that the beauty of the language of Ibn Zaidun's poetry will be seen, so that we can find out the form of the beauty of the famous poetry at that time.